Noise coupling reduction using temperature enhanced device for future integrated circuit integration applications - Siva Kumar, Malagonda; Mohanraj, Jayavelu (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
Information technology-to-internet of things may have succeeded because of fast silicon chip capability expansion. Moore's law, which reduces device size, boosted integrated circuit (IC) performance. Delay rises with highdensity connection parasitic capacitance. Interconnect delays have surpassed transistor delays and slowed progress. An alternative is required now to reduce connection latency. The third dimension is used in popular 3D IC technology IC technology requires through silicon via (TSV) for signal integrity and heat mitigation. Noise coupling hinders electrical communication between signal-carrying TSVs (aggressive TSVs) and ground TSVs (victim TSVs), a 3D IC bottleneck. TSVs must be dielectrically insulated from Si substrates to avoid electrical signal interference. Additionally, first-order modelling will confirm the suggestions. This article proposes using the nanosheet field effect transistor (NSFET) to overcome 3D IC noise coupling and complementary metal oxide semiconductor (CMOS) technology nodes. After discussing the electronic industry and sub nm, several basic metrics and criteria for developing electronic components are presented. The first technique uses Perylene-N's exceptional noise-cancelling characteristics. Second technique uses electrical TSV (ETSV), thermal TSV (TTSV), and heat source models to measure noise coupling on numerous ICs. The third proposes many noise-reducing materials. The suggested structures outperform traditional approaches.